5th Thessaloniki Biennale of Contemporary Art : Old Intersections - Make it New III. - Bolis, Yannis; Christoforidou, Kleoniki; Gounari, Doman; Thessaloniki Biennale of Contemporary Art Thessaloniki 2015; Koskina, Katerina; Gregos, Katerina (Thessaloniki : State Museum of Contemporary Art, 2015)
Aires, Carlos ; Day, Jeremiah ; Altay, Can ; Argote, Ivan ; Arsanios, Marw ; Bak, Bertille ; Batniji, Taysir ; Beckett, James ; Esber, Ninar ; Fatmi, Mounir ; Friedl, Peter ; Garabedian, Mekhitar ; Hannes, Nick ; Van Lieshout, Erik ; et al.
5th Thessaloniki Biennale of Contemporary Art, Thessaloniki, 23/6 - 30/9/2015
kunstcatalogus